Comparison of immunomodulatory factors produced by mesenchymal stem cells in multiple sclerosis patients and healthy controls - Thevathas, Sarah (2018)
Mesenchymal Stem Cells (MSCs) have been identified as playing vital a role in the modulation of the immune system (Rivera and Algner, 2012). Here we aimed to characterise the role of MSC as immunomodulators of peripheral blood mononuclear cells (PBMC) and to measure the immunomodulatory effects of MSCs from MS patients and determine whether they are less pronounced than those from healthy controls (HC). Methods: MSCs from secondary progressive MS patients and HCs were isolated by bone marrow aspiration using Ficoll density centrifugation. Autologous PBMC were activated alone and together with MSCs using 1µg anti-CD3 and 1µg/ml anti-CD28. After 72hrs activation and 5hrs of re-activation with PMA-ionomycin-brefeldinen A, they were stained intracellularly for the inflammatory cytokines IL-17, IFN-γ, and GM-CSF. Cytokine expression was then quantified using flow cytometry. Immunomodulatory functions in MSCs are known to be exerted through cytokines so cytokine profiling of MSCs from MS patients and HCs was also carried out, where cytokines and chemokines with known immune function were measured. Results: Activated PBMCs from MS patients in culture with autologous MSCs significantly (p=0.01) increased the percentage of IL-17. The percentage of IL-17+ cells was significantly (p=0.046) decreased in PBMC from HCs co-cultured with autologous MSC. The expression of IFN- by PBMC of healthy volunteers (n=7) was numerically but not statistically significantly higher than that of PBMC (n=5) from the volunteers with SPMS participating in this study. Cytokine profiling showed decreased IL-8 and IL-10 levels in MS-MSC supernatants compared to controls (p=0.03). No differences were seen in the proportion of IL-6, IL-1, TNF-, and GM-CSF between HC or MS patients. Conclusion: MSCs show great promise in therapeutic use in MS. However, this study shows large variability in the results. There is a possibility that MSCs from MS patients could be defective in their immunoregulatory ability, in regards to the Th17 subset. The translation to therapeutic clinical trials is feasible, but it will require caution and monitoring.